The Online Teaching Learning Platform (PK Learning): Students’ Perspective - Suryani, Latifah; Hikmat, Mauly Halwat; Maryadi, Maryadi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
Online learning will most certainly have an important role to play in future learning. E-learning courses come in a variety of formats and utilize a range of technologies. E-learning enables students to complete training and educational objectives with greater ease and flexibility. PK Learning is an online education with an interactive and self-paced form of learning that can be used by Muhammadiyah Program Khusus to learn anytime, anywhere. This study described middle-school students’ attitudes toward the use of PK Learning from its accessibility, flexibility, and effectiveness. There is one class in each grade consisting of 30 or 31 students, which was used to collect the data, which means that 93 students from grades 7, 8, and 9 participated in this research. The data was collected in the form of a descriptive case study with interviews and observation. The purpose of this study was to explore the student’s perception of the use of PK Learning. Analysis percentage and the result of the interview were used to capture the responses. Analysis of the data revealed three major positive perceptions toward PK Learning: accessibility, flexibility, and effectiveness. Based on the findings, The use of PK Learning from students’ perceptions in the Muhamamadiyah Program at Khusus Junior High School is discussed.